2019
DOI: 10.1177/1545968319836207
|View full text |Cite
|
Sign up to set email alerts
|

Camera-Based Mirror Visual Input for Priming Promotes Motor Recovery, Daily Function, and Brain Network Segregation in Subacute Stroke Patients

Abstract: Background. Camera technique-based mirror visual feedback (MVF) is an optimal interface for mirror therapy. However, its efficiency for stroke rehabilitation and the underlying neural mechanisms remain unclear. Objective. To investigate the possible treatment benefits of camera-based MVF (camMVF) for priming prior to hand function exercise in subacute stroke patients, and to reveal topological reorganization of brain network in response to the intervention. Methods. Twenty subacute stroke patients were assigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 60 publications
2
32
0
7
Order By: Relevance
“…Studies have shown the activation of the ipsilateral motor cortex (ipsilateral to the training hand and contralateral to the MVF) caused by MT ( Saleh et al, 2017 ; Bai et al, 2019a ). The activation of frontal regions, for example, premotor area, and parietal regions, has been also reported in previous literature ( Hamzei et al, 2012 ; Saleh et al, 2017 ; Bai et al, 2019a ; Ding et al, 2019 ). However, the intercortical functional connectivity when receiving MT is seldom investigated, which is of importance to understand the role of MNS in MT-related neural networks.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Studies have shown the activation of the ipsilateral motor cortex (ipsilateral to the training hand and contralateral to the MVF) caused by MT ( Saleh et al, 2017 ; Bai et al, 2019a ). The activation of frontal regions, for example, premotor area, and parietal regions, has been also reported in previous literature ( Hamzei et al, 2012 ; Saleh et al, 2017 ; Bai et al, 2019a ; Ding et al, 2019 ). However, the intercortical functional connectivity when receiving MT is seldom investigated, which is of importance to understand the role of MNS in MT-related neural networks.…”
Section: Introductionsupporting
confidence: 84%
“…Strengthened connectivity among bilateral premotor and ipsilateral motor areas may indicate that the effect of MVF-based observation motor learning could be enhanced when it is in combination with iTBS over the motor cortex. A previous clinical study about the effects of MT on functional connectivity in patients with stroke, identified significant connectivity enhancement at resting state, over premotor, motor, and parietal areas bilaterally ( Ding et al, 2019 ), in patients who received 10-session MT. Therefore, in order to yield maximal benefits for patients, there needs to be further investigation to determine an optimal dose of MT intervention when it is applied in different clinical populations with suitable priming techniques that can be combined with.…”
Section: Discussionmentioning
confidence: 96%
“…According to an fMRI study, supplementary activation was found in visual areas during MVF (Matthys et al, 2009). Our previous study also showed that after the intervention of MVF, an increase in communication efficiency was found in the visual area in stroke patients (Ding et al, 2019a). These might suggest visual inputs as a crucial basis for this approach.…”
Section: Alterations Of Brain Activitiesmentioning
confidence: 88%
“…It plays a critical role in mental life, closely relating to the sense of self (Longo et al, 2008). Studies suggested that embodiment has the potential to alter patients' sensorimotor activity and multisensory integration (Michielsen et al, 2011;Saleh et al, 2014;Medina et al, 2015;Ding et al, 2019a). Wainer et al reported that embodiment could affect patients' engagement of robot-supported training and suggested a positive correlation between the experience of embodiment and effectiveness of treatment (Wainer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Illusions stemming from rubber hand, mirror visual feedback (MVF), and VR have been suggested to evaluate aspects of embodiment (14)(15)(16)(17). Research on stroke rehabilitation demonstrate that the experience of embodiment during these visual stimulations, like MVF, has the potential to alter the patient's sensorimotor activity and contribute to motor recovery (18)(19)(20). Studies reported that MVF priming had an instant effect on neural modulation and a long-term effect on neural plasticity, which was recognized as the underlying therapeutic mechanism (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%